Childhood soft tissue tumors, one center experience (Annals of Medical Research, 2021)
Aim: Studies on childhood soft tissue tumors have generally been conducted with malignant tumors. There are few studies in the literature comprising all soft tissue tumors. The current study aimed to examine the incidence of all benign and malignant soft tissue tumors during childhood in East Mediterranean region.Materials and Methods: This study retrospectively analyzed the data gathered from patients diagnosed with soft tissue tumors according to the WHO 2020 classification. It focused on those aged 0–18 years that underwent excisional biopsy at Adana City Training and Research Hospital (Adana, Turkey) between 2014 and 2020.Results: Of the total patients, 47.5% were female and 52.5% male. Of these, 87.2% of the cases were benign, 9.2% malignant, and 3.6% intermediate. Hemangioma (55%) was the most common benign soft tissue tumor, and the most common location was the head–neck. Other benign soft tissue tumors were neurofibroma (8.8%), lipoma (6.1%), schwannoma (5.1%), and neuroma (4.4%). Rhabdomyosarcoma (53.2%) was the most common malignant soft tissue tumor. The embryonal subtype was the most common (36.6%). Other malignant soft tissue tumors were extra-osseous PNET/Ewing’s sarcoma (16.6%), synovial sarcoma (13.3%), and leiomyosarcoma (3.3%).Conclusion: Similar to the literature, in this study, the most common benign soft tissue tumor in children was hemangioma, and the most common malignant soft tissue tumor was rhabdomyosarcoma. It is hoped that this study will contribute to the literature as it is the first study to cover all childhood soft tissue tumors at national and regional scale.
Keywords: Childhood; neoplasms; soft tissue